Surgical correction of unilateral ankylosis of the temporomandibular joint; Case report - Viera, Kemberly Gabriela (2019)
The unilateral ankylosis of the temporomandibular joint corresponds to a temporomandibular disorder classified within the chronic mandibular hypomobility. The objective of the present clinical case, to provide a clinical and diagnostic guide on this pathology, for the dental community, providing a new alternative so that this anomaly can be corrected and hand improve the quality of life of our patient, with a treatment One hundred percent scientific, professional and guaranteed. The literature defines ankylosis as an abnormal immobility of the jaw, disorder that leads to a restriction of the buccal opening with partial reduction of mandibular movements or a complete immobility of the jaw. We present a case of unilateral temporomandibular ankylosis (left) in a 14-year-old boy, who treated with ankylosing block resection, after mandibular fracture in order to elongate the soft tissues and maintain space in the new glenoid cavity to avoid re-ankylosis and favor the remodeling of the condyle.